2020
DOI: 10.18203/2394-6040.ijcmph20200973
|View full text |Cite
|
Sign up to set email alerts
|

Assessing level of pre and post interventional knowledge and attitude for dengue awareness among selected government school student of Bhopal, India

Abstract: Background: Dengue is a major public-health issue all over tropical and sub-tropical regions of the world. It is the most rapidly spreading mosquito-borne viral disease, which shows a 30-fold increase in global incidence over the past 50 years. According to the estimates from the World Health Organization 50-100 million dengue infections occur each year and that to add to the seriousness that around 50% of the world’s population lives in countries where the disease is endemic.Methods: Educational Interventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Another interesting finding in this review is that despite a significant association between knowledge of dengue and attitude towards Aedes mosquito control, some studies have reported that good knowledge and good practice may be unparallel. However, other studies have reported similar levels of association [ 95 , 96 ], with few others citing positive association [ 97 , 98 ]. Although the exact factor that inhibits the translation of dengue knowledge to preventive practice is unknown, we hypothesised several major factors based on the rationale and analysis of the reviewed articles.…”
Section: Discussionmentioning
confidence: 70%
“…Another interesting finding in this review is that despite a significant association between knowledge of dengue and attitude towards Aedes mosquito control, some studies have reported that good knowledge and good practice may be unparallel. However, other studies have reported similar levels of association [ 95 , 96 ], with few others citing positive association [ 97 , 98 ]. Although the exact factor that inhibits the translation of dengue knowledge to preventive practice is unknown, we hypothesised several major factors based on the rationale and analysis of the reviewed articles.…”
Section: Discussionmentioning
confidence: 70%